Development of tolerance upon repeated administration with the GABAB receptor positive allosteric modulator, COR659, on alcohol drinking in rodents. (2nd November 2022) - Lorrai, Irene; Shankula, Chase; Marquez Gaytan, Jorge; Maccioni, Riccardo; Lobina, Carla; Maccioni, Paola; Brizzi, Antonella; Mugnaini, Claudia; Gessa, Gian Luigi; Sanna, Pietro Paolo; Corelli, Federico; Colombo, Giancarlo
ABSTRACT: Background: Recent work has demonstrated that acute administration of the novel positive allosteric modulator of the GABAB receptor, COR659, reduces several alcohol-related behaviors in rodents. Objective: To assess whether COR659 continues to lessen alcohol intake after repeated administration, a fundamental feature of drugs with therapeutic potential. Methods: Male C57BL/6J mice (n = 40) were exposed to daily 2-hour drinking sessions (20% (v/v) alcohol) under the 1-bottle "drinking in the dark" protocol and male Sardinian alcohol-preferring rats (n = 40) were exposed to daily 1-hour drinking sessions under the 2-bottle "alcohol (10%, v/v) vs water" choice regimen. COR659 (0, 10, 20, and 40 mg/kg in the mouse experiment; 0, 5, 10, and 20 mg/kg in the rat experiment) was administered intraperitoneally before 7 consecutive drinking sessions. Results: Alcohol intake in vehicle-treated mice and rats averaged 2.5–3.0 and 1.5–1.6 g/kg/session, respectively, indicative of high basal levels. In both experiments, treatment with COR659 resulted in an initial, dose-related suppression of alcohol intake (up to 70–80% compared to vehicle treatment; P  < .0005 and P  < .0001 in mouse and rat experiments, respectively). The magnitude of the reducing effect of COR659 on alcohol drinking diminished progressively, until vanishing over the subsequent 2–4 drinking sessions. Conclusion: COR659 effectively reduced alcohol intake in two different rodent models of excessive alcohol drinking. However, tolerance to the anti-alcohol effects of COR659 developed rapidly. If theoretically transposed to humans, these data would represent a possible limitation to the clinical use of COR659.